2019
DOI: 10.2196/10924
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Patient-Reported Outcome Measures and the Severity of Chronic Obstructive Pulmonary Disease in the Context of an Innovative Digitally Supported 24-Hour Service: Longitudinal Study

Abstract: Background Individuals with chronic obstructive pulmonary disease (COPD) live with the burden of a progressive life-threatening condition that is often accompanied by anxiety and depression. The severity of the condition is usually considered from a clinical perspective and characterized according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification of severity (1-4) and a risk assessment (A through D) that focuses on the patient’s symptoms and number of exacerbation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
5
1
Order By: Relevance
“…Our results are in accordance with our previous finding that the participants’ emotional distress decreases over time [ 25 ]. The reduced number of contacts to the RCC may also reflect the finding that the participants reported a perception of being less active in managing their condition [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are in accordance with our previous finding that the participants’ emotional distress decreases over time [ 25 ]. The reduced number of contacts to the RCC may also reflect the finding that the participants reported a perception of being less active in managing their condition [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with our previous finding that the participants’ emotional distress decreases over time [ 25 ]. The reduced number of contacts to the RCC may also reflect the finding that the participants reported a perception of being less active in managing their condition [ 25 ]. Based on both the previous findings and the number of contacts, will we hypothesize that the ECM living lab environment and service ecosystem contributes to the participants ability to better manage the COPD and related challenges.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nonetheless, the maintenance of these changes needs to be determined. Other longitudinal studies related to individuals with chronic obstructive pulmonary disease have shown that on scale 3, the main scores decreased after 6 and 12 months [ 28 ]. Scales 1, 4, 5, 8, and 9 did not significantly differ between T0 and T1.…”
Section: Discussionmentioning
confidence: 99%